Utilization of Duo lingo Application used and Practice Drilling Vocabulary Technique for Up-Grading Students’ Reading Comprehension - Mas Dahlan; Nurbianta Nurbianta (Journal of English Education and Linguistics, 2020)
English language has been commonly accepted as an active universal language in the world. People who study English language consider it as their personal proficiency. Therefore, nowadays many people, particularly students, ought to master English language. Mastering English language is an important value for the students to have. Refers to the condition, the researcher interested to help student to master English specially reading comprehension, and this research would find the following questions; Is there any influence of duolingo application used to the students’ reading comprehension at SMA Muhammadiyah Tanjung Redeb?, (1) Is there any influence of vocabulary enhancement to the students’ reading comprehension at SMA Muhammadiyah Tanjung Redeb?, (1) Is there any influence of duolingo application used and vocabulary enhancement to the students’ reading comprehension at SMA Muhammadiyah Tanjung Redeb?. The method of this research is partial correlation method, then to analyze the data used normality, homogeneity, linearity, partial correlation and regression equation.